Nature and possible origins of hyper-arid floodplain islands: exemplified by the Kuiseb river, Namibia. Issue 2 (4th May 2018) - Ringrose, Susan; Seely, Mary; Matheson, Wilma; Cassidy, Lin; Kemosidile, Thebe; Diskin, Sorcha; Coetzee, Stephan
Abstract : The present work considers morphological and sedimentary evidence from floodplain island sediments in the ephemeral Kuiseb river of central coastal Namibia. Morphologically the islands constitute point bars, curvilinear ridges and composite megaforms. The island sediments consistently comprise two lithofacies – a lower relatively thick often massive silt-very fine sand which is overlain by an upper, thinner, intermittent fine sand. The structure and texture of the lower beds suggest that early island deposition took place as a series of mass flows in association with low velocity stream flow. Originating from pre-existing upstream silt and very fine sand, the mass flows appear to have entered the main Kuiseb valley under unusual conditions of relatively heavy, coastal rainfall during the generally drier conditions of the Little Ice Age. Upon desiccation the sediments were soon partially indurated due to extreme evaporation effects. The upper fine sand lithofacies are regarded as being the product of more recent major flood events. The fine sands were deposited as a result of upper catchment rainfall leading to the formation of mainly overbank and levee deposits, in addition to eroding the islands into their current morphology. Hence the Kuiseb floodplain islands are characterised as hybrid deposits reflecting changing palaeo-climatic conditions over the last 600 years or so. This type of hybridisation involving infrequent earlier mudflow deposition, the induration and retention of the deposits and their later modification by renewed flooding, might be regarded as an important characteristic of moderate to low energy hyper-arid rivers worldwide.